SOIL IS A THERMODYNAMIC SYSTEM AND SUBSTANTIATION OF ITS HOMEOSTASIS CONCEPT - Коломиец, Сергей; Белоброва, Анастасия (SWorldJournal, 2020)
The purpose of the publication is to reveal the internal processes carried out in the soil in interaction with cyclically changing external climatic factors and to prepare the concept of soil homeostasis. Methods of synergetic and thermodynamic, experimen